PENERAPAN METODE KESEHARIAN PADA DESAIN KAMPUNG SUSUN SEBAGAI STRATEGI PERBAIKAN PERMUKIMAN DI KAMPUNG APUNG - O’Brien Sameagan Tandika; Irene Syona Darmady (Jurusan Arsitektur dan Perencanaan, 2022)
Kampung Apung is located in Cengkareng District, which is one of the sub-districts that is often affected by annual floods. In addition, the land around Kampung Apung was elevated twice due to the construction for industrial factories and warehouses resulted in the houses of the residents of Kampung Apung being lower than the surrounding area, as a result, Kampung Apung was permanently flooded. Many residents of Kampung Apung began to move due to permanent flooding, but there were also residents who chose to stay because of the collective memory in Kampung Apung. Although the residents of Kampung Apung have adapted to the surrounding environment, this still results in the residential buildings continuing to experience physical degradation and has a direct impact on the quality of life of the residents of Kampung Apung, for example, lack of access to clean water, semi-permanent buildings that must be repaired regularly, to waste problems due to permanent flooding. As a result, the quality of life of the residents of Kampung Apung continues to deteriorate over time. The ultimate goal of this project is to improve the quality of life for the residents of Kampung Apung by providing affordable housing designed using the “everydayness” method to produce housing with additional programs based on the daily lives of the residents of Kampung Apung. The final form of the project is vertical housing in the strategy of Kampung Susun. Keywords: Degradation; Everydayness; Kampung Susun; Life Quality Abstrak Kampung Apung terletak di Kecamatan Cengkareng, yang merupakan salah satu kecamatan yang sering terdampak banjir tahunan. Peninggian tanah di sekitar Kampung Apung sebanyak dua kali akibat pembangunan pabrik industri dan pergudangan mengakibatkan rumah warga Kampung Apung lebih rendah dibandingkan sekitar, akibatnya Kampung Apung terendam banjir permanen. Banyak warga Kampung Apung yang mulai berpindah akibat banjir permanen, tetapi ada juga warga yang memilih bertahan karena adanya memori kolektif di Kampung Apung tersebut. Walaupun warga Kampung Apung telah beradaptasi dengan lingkungan sekitarnya, hal ini tetap mengakibatkan bangunan hunian terus mengalami degradasi fisik dan berdampak langsung pada kualitas hidup warga Kampung Apung, misalnya akses air bersih yang kurang, bangunan semi-permanen yang harus dibenahi secara rutin, hingga permasalahan sampah akibat banjir permanen. Akibatnya, kualitas hidup warga Kampung Apung terus memburuk seiring berjalannya waktu. Tujuan akhir proyek ini adalah untuk meningkatkan kualitas hidup warga Kampung Apung dengan menyediakan hunian terjangkau yang didesain menggunakan metode “keseharian” agar menghasilkan hunian dengan program tambahan berdasarkan keseharian warga Kampung Apung. Bentuk akhir proyek berupa hunian vertikal dengan strategi Kampung Susun.